Pengembangan E-book Interaktif Sebagai Sumber Belajar Mandiri Pada Materi Pemuaian Kelas VII SMP/MTs - Aretha Amalia; Dinar Maftukh Fajar (VEKTOR: Jurnal Pendidikan IPA, 2021)
The development of interactive e-book as a source of self-learning on the material thermal expansion of the class VII SMP/MTs was carried out based on problems that occurred in one of junior high schools in Songgon, Banyuwangi, East Java, Indonesia. During the online learning process on thermal expansion material, science teachers used printed textbooks and learning videos, but students still had difficulty understanding the material from these two sources. One of the reasons is the lack of interactivity of both sources. The purpose of this study is to describe the results of the validation and student responses to the interactive e-book as a source of self-learning in the VII grade junior high school on thermal expansion material. The research and development design uses Thiagarajan's (1974) 4D model which consists of 4 stages including define, design, develop, and disseminate, but this research is limited to the develop stage. The subjects in this study consisted of 2 lecturers of UIN KHAS Jember as material and media experts, 2 science teachers as user experts and the response test was carried out on 32 students. The results of the validation of experts and users were found to be an average of 92.5% and 92.43%, it shows that interactive e-book as a self-learning resource are declared very valid to be used. The results of student responses have an average score of 90.58%. Descriptions of student responses are explained in the form of wordcloud where most students consider that the interactive e-book developed is "good" because it is equipped with writing, pictures, videos, animations, and practical simulations.